1990
DOI: 10.1139/v90-006
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the charge density of acrylamide/acrylate copolymers by tensammetry

Abstract: TRUIS SMITH-PALMER and BYRON R. WENTZELL. Can. J. Chem. 68, 26 (1990). The charge densities of acrylamide/acrylate copolymers can be determined using tensammetry. The tensammograms were run using 20 ppm solutions of polymer in 0.1 M tetraethylammonium chloride. A standard curve of desorption peak height versus mol% anionicity was useful in the range 10-50%. A second standard curve of the potential at which the capacitive current measured 1 pA versus mol% anionicity allowed the determination of charge density i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…reported previously for polyacrylamide (9). Thus we can say that the adsorption of these polymers onto a neutral or a negatively or positively charged mercury surface is independent of molecular weight.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…reported previously for polyacrylamide (9). Thus we can say that the adsorption of these polymers onto a neutral or a negatively or positively charged mercury surface is independent of molecular weight.…”
Section: Resultssupporting
confidence: 60%
“…We have previously shown that we can determine the concentration of polyacrylamides and cationic and anionic acrylamide copolymers using both polarographic maximum suppression (8) and tensammetry (6), and that we can use tensammetry to determine the mol% anionicity of anionic acrylamidelacrylate copolymers after complexation with tetraethylammonium chloride (9). In this paper we compare the tensammetric behaviour of various cationic polymers and copolymers in order to study parameters which affect their adsorption at various potentials.…”
Section: Introductionmentioning
confidence: 99%